Health and Gender Medicine Clinic: 2 years of multidisclipinary team experience. (30th September 2020) - Pasqualini, P; Rizzo, L; Facchi, E; Culicchi, V; Lenzi, L; Mucci, D; Erba, F; Moscatelli, C; Pagliara, C; Doretti, V
Abstract: Background: Cardiovascular disease (CVD) is the leading cause of mortality in western countries and the first cause of mortality in women. Purpose: Women generally do not concern about CVD and that represents the main risk for them. Methods: Misericordia Hospital, Grosseto, started a Clinic of Health and Gender Medicine on 2017. On the first and third Monday of every month, we evaluate < 60 years patients who are at risk for traditional CVD, depression, early menopause, polycystic ovary, autoimmune and rheumatic disease. On the first visit, medical history, arterial pressure, electrocardiogram, body mass index, waist circumference and lipid profile, were collected. We also supply questionnaires to evaluate diabetes and depression risk by Generalized Anxiety Disorder (GAD-7), Patient Health Questionnaire (PHQ-9) and food diary. Two weeks later, a multidisciplinary team (cardiologist-diabetologist-nutritionist-gynecologist-psychiatrist and a nurse) evaluates the patients defining the personal risk profile. Results: From 2017 to December 2019, 74 females and 7 males belonging to the target population were examined. Age group: <45(61%), 46-50(26%), 51-60(48%), >60(19%). Clinical characteristics: Hypertension: 64%; Obesity 5%; Unknown dyslipidemia 44%; Risk of diabetes: 39%; Gestational diabetes: 5%; Gestational hypertension: 5% CVD risk: 42%; Depression: 33% Autoimmune disease: 30%. From them 60.5% have needed further investigation. Follow-up is going on. Conclusions: according with the literature, more than 50% of the cohort was unconsciously at high risk of CVD. So a multidisciplinary approach is needed in order to frame a complex health status. Thus we established collaboration with patients to improve lifestyles as CVD-prevention's tool. Key messages: Cardiovascular disease represent often an hidden health problem, especially in women. Multidisciplinary approach is needed to face CVD.